Labour Standards and Trade: In Search of Impact and Alternative Instruments - Orbie, Jan (2017)
Labour standards have become an almost routine feature of trade agreements. However, we have little knowledge about whether this linkage is effective; both in absolute terms but also in comparison to other instruments that promote labour standards on a global level. Such alternative instruments include public-private agreements, value chain management and procurement policies. The articles in this thematic issue will provide insights that further the debate on the effectiveness of the connection between labour rights and international trade, looking at both ‘traditional’ trade agreements and ‘alternative’ instruments.